An open chat with…Alexander Wlodawer - Ioannis Tsagakis; Alexander Wlodawer (FEBS Open Bio, 2022)
Alexander Wlodawer has been a member of the FEBS Open Bio Editorial Board since the journal's launch in 2011. Currently, he is Senior Investigator at the Center for Structural Biology, National Cancer Institute in Frederick, Maryland, USA. He received his Ph.D. from the University of California, Los Angeles in 1974, completed postdoctoral training at Stanford University and has also worked at the National Bureau of Standards, the ABL‐Basic Research Program at the NCI‐FCRDC and the University of Cambridge, UK. He is Doctor Honoris Causa of the Technical University of Lodz, Poland. Alexander Wlodawer is also a recipient of the 2006 NCI Mentor of Merit Award, was awarded the Heyrovsky Honorary Medal by the Czech Academy of Sciences in 2008, was elected Foreign Member of the Polish Academy of Sciences in 2005, and has been member of the Editorial Board of The FEBS Journal since 2007. He is currently Editor‐in‐Chief of the journal Current Research in Structural Biology. In this compelling interview, he shares with us his experiences on solving the structures of IL‐4 and retroviral proteases, advice on how to deal with being scooped, and his thoughts on open data sharing and AlphaFold.